The Impact of Pedagogical Translanguaging on Students’ Learning in EFL Classrooms - Supriadin; Amrullah Abduh; Muhammad Basri; Geminastiti Sakkir; Sultan Baa (Universitas Islam Negeri Palopo, 2026)
Translanguaging pedagogy, regarded as a contemporary trend in 21st-century bilingual and multilingual education, prompts EFL teachers to embrace this technique to facilitate the students' learning of the target language by employing their entire linguistic repertoire. This study seeks to examine the impacts of employing translanguaging pedagogy on students’ learning in English as a foreign language classroom in Indonesian high schools. The study examines how translanguaging pedagogy supports the students in English language learning particularly to the weaker of English language proficiency. This study utilized a multiple case study with three English educators and 50 secondary school students in Indonesia. Data were gathered using surveys and direct observation. The results indicate that translanguaging promotes students' English proficiency and improves their communication skills in the target language. Moreover, translanguaging pedagogy enhances students' vocabulary acquisition, promotes active engagement in EFL classrooms, facilitates meaningful learning experiences, and encourages motivation and support among students. Thus, the researchers recommend incorporating translanguaging in EFL teaching, as this approach is deemed essential and beneficial from various multilingual perspectives.